An almost sure central limit theorem for self-normalized partial sums of weakly dependent random variables. Issue 12 (17th June 2016) - Lin, Zhengyan; Pang, Tian-Xiao; Hwang, Kyo-Shin
Abstract: We give here an almost sure central limit theorem for self-normalized partial sums of a strictly stationary φ-mixing sequences which is in the domain of attraction of the normal law with mean zero and possibly infinite variance. Our result substantially extend a result on the almost sure central limit theorem previously obtained by Huang and Pang (2010).